The Post–Great Recession Geographies of U.S. Municipal Borrowing and Indebtedness. Issue 2 (3rd April 2021) - Davidson, Mark; Lukens, David; Ward, Kevin
Abstract : Borrowing from capital markets has a long history in U.S. urban government. With federal authorities withdrawing fiscal support since the 1980s, U.S. cities have become more entrepreneurial and increased their reliance on borrowing. Some now claim that this reliance has grown since the Great Recession. Despite the significance of borrowing to U.S. urban governments, municipal indebtedness remains a relatively understudied topic within geography. This article examines post–Great Recession indebtedness changes (2006–2016) in the general funds of U.S. municipalities. We show that general fund indebtedness has not generally increased since the Great Recession, although a complex landscape of divergent borrowing and indebtedness is evident across cities with different populations. The article uses the Government Finance Database to collect and analyze U.S. Census Bureau data on municipal debt and budget health. We conclude by discussing the need to develop existing theories of postrecession urban governance to examine emerging debt and budgetary challenges across U.S. municipalities.